Sion and Elizium: National Identity, Religion, and Allegiance in Anthony Copley’s A Fig for Fortune - Underwood, Lucy (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2018)
This article uses Anthony Copley’s poem A Fig for Fortune (1596) to examine Elizabethan constructions of national identity. Acknowledging that religious and national identities were symbiotic in the Reformation era, it argues that the interdependency of Protestant and Catholic narratives of “nationhood” must be appreciated. Analysis of Copley’s text engages with previous critiques, including those of Clare Reid, Alison Shell, and Susannah Monta, in order to propose a more coherent interpretation of Copley’s engagement with Spenser’s The Faerie Queene. Copley did not merely defend Catholics as loyal subjects; he moved beyond debates about loyalty to reconsider ideas of nation, England, and Englishness more broadly, challenging the premises as well as the conclusions of Protestant statesmen and writers.